Energy absorption and inelasticity distribution mechanisms in steel moment frames affected by mainshock-aftershock sequences. (October 2021) - Torfehnejad, Mohammadmehdi; Sensoy, Serhan
Abstract: This study evaluates the effect of earthquake shock sequences on the collapse mechanism of Special Steel Moment Frames (SSMFs) by studying the distribution of plasticity and hysteretic energy parameters. For this purpose, four SSMFs with 4–20 stories are numerically modelled in OpenSees and subjected to incremental dynamic analysis (IDA). These analyses aim to capture the collapse state of structures under aftershock events preceded by various mainshock levels. The distribution of Maximum Ductility Demand (MDD) and Energy Absorption Contribution (EAC) at the collapse state is then evaluated in presence of sequential shocks. The results show that the EAC parameter provides better metric for studying the collapse mechanism which is remarkably affected by the mainshock-aftershock sequence. Accordingly, the role of elements experiencing damage under the mainshock becomes less prominent in absorbing the aftershock energy and is substituted by contribution of elements with less deterioration under the mainshock. The members' EAC is also shown to be affected by the percentage of the energy imposed by each individual shock as a fraction of the total energy imposed by the mainshock-aftershock sequence. In overall, for low-rise structures subjected to aftershock-only excitation, almost equal EACs are provided by the beams and columns while beams' EAC is shown to exceed 60% for high-rise structures due to their flexural load bearing mechanism. With introduction of the mainshock damage, however, the dependency of the EACs to the structures' height becomes less significant.